CCAAT/Enhancer-binding Protein Homologous Protein Promotes ROS-mediated Liver Ischemia and Reperfusion Injury by Inhibiting Mitophagy in Hepatocytes. Issue 1 (13th July 2022) - Zhou, Shun; Rao, Zhuqing; Xia, Yongxiang; Wang, Qi; Liu, Zheng; Wang, Ping; Cheng, Feng; Zhou, Haoming
Abstract : Background: Liver ischemia and reperfusion (IR) injury represent a major risk factor in both partial hepatectomy and liver transplantation. CCAAT/enhancer-binding protein homologous protein (CHOP) is a key regulator of cell death, its precise molecular basis in regulating hepatocyte death during liver IR has not been delineated. Methods: Hepatocellular CHOP deficient mice were generated by bone marrow chimera models using global CHOP knockout mice. Liver partial warm ischemia model and hypoxia/reoxygenation model of primary hepatocytes were applied. Liver injury and mitophagy-related signaling pathways were investigated. IR-stressed patient liver tissues and serum samples were analyzed as well. Results: Mice with hepatocellular CHOP deficiency exhibited alleviated cell death, decreased reactive oxygen species (ROS) expression, and enhanced mitophagy in hepatocytes after IR, confirmed by in vitro studies of hepatocytes after hypoxia/reoxygenation. Mitochondria ROS scavenge by Mito TEMPO effectively attenuated hepatocyte death and liver IR injury of wild-type mice, whereas no significant effects were observed in hepatocellular CHOP -deficient mice. CHOP depletion upregulated dynamin-related protein 1 and Beclin-1 activation in the mitochondria of hepatocytes leading to enhanced mitophagy. Following IR, increased CHOP expression and impaired mitophagy activation were observed in the livers of patients undergoing hepatectomy. N-acetyl cysteine pretreatment significantly improved the liver function of patients after surgery. Conclusions: IR-induced CHOP activation exacerbates ROS-mediated hepatocyte death by inhibiting dynamin-related protein 1–Beclin-1–dependent mitophagy.